The Effect of Standardized Mangosteen Skin Extraction, Nano-emulsion, Nano-chitosan and Treadmill Exercise on Atherogenic Rat Model - Andreas Ari Setiawan; Agung Priyono; Gabriela Rolanda; Yoannesviane Eric Pratama (RSUP Dr. Kariadi, 2024)
Background: Atherosclerosis, the most common cause of CVD, is associated with oxidative stress and cholesterol. Antioxidant and regular physical exercise have been considered as the probable interventions to dampen the process. The pericarp of mangosteen (Garcinia mangostana Linn) is known for containing a high amount of xanthones including α-mangostin with antioxidant effects. The current study investigates the anti-atherogenic potential of mangosteen skin extract in nano-emulsion and nano-chitosan formulations, singly and in combination with treadmill exercise, versus the statin, Atorvastatin. Methods: A randomized controlled trial was conducted on 30 male Wistar rats, divided into six groups: normal diet control (C1), atherogenic diet control (C2), and four treatment groups receiving an atherogenic diet plus treadmill exercise combined with Atorvastatin (T1), standardized mangosteen extract (T2), mangosteen nano-emulsion (T3), or mangosteen nano-chitosan (T4). The aortic tunica intima and tunica intima-media thickness were measured histologically after 56 days. Results: The aortic intimal thickness was noticeably higher in the atherogenic diet group (C2: 12.13±1.87 mm) compared to the normal diet group (C1: 4.27±0.75 mm). In the treatment groups, the intimal thickness ranged from 2.97±0.45 mm to 4.17±1.70 mm and showed no significant differences from the normal diet group. A similar pattern was seen in the intima-media thickness, with 145.63±17.12 mm recorded for the normal diet group and values ranging from 106.90±10.41 mm to 135.90±12.63 mm in the treatment groups, again without significant differences. Survival analysis using Kaplan-Meier curves showed clear differences between the groups (p < 0.001). The untreated atherogenic diet group (C2) had the poorest survival, with no rats surviving until the study's conclusion. In contrast, survival improved in all treatment groups, with the Mangosteen Nano-chitosan (T4) group and the normal diet group (C1) achieving the best outcomes, as all rats in these groups survived. Conclusion: Mangosteen skin extracts, whether in nano-emulsion or nano-chitosan forms, combined with treadmill exercise, showed significant differences in maintaining the survivability of rat with atherogenic-induced diet despite no significant differences in preventing atherogenesis compared to Atorvastatin or a normal diet. Further research is needed to confirm these potential therapeutic effects.